Hybrid Effect of PVA Fibre and Carbon Nanotube on the Mechanical Properties and Microstructure of Geopolymers - Tao Meng (Frontiers Media S.A., 2021)
The concept of geopolymers has been widely studied since it was proposed. However, the wide range of applications of geopolymers is affected by brittleness and poor crack resistance. In this study, the mechanical properties of geopolymers with single-doped PVA fibres, single-doped carbon nanotubes, and mixed PVA fibers and carbon nanotubes were studied respectively first. It was found that PVA fibres and carbon nanotubes had a positive effect on improving the mechanical properties of geopolymers, especially bending strength and flexural strength. Moreover, the incorporation of PVA fibre could improve the damage morphology of geopolymers. Additionally, the phase analysis, structural group analysis, and strengthening mechanism were studied via scanning electron microscopy, mercury intrusion porosimetry analysis, X-ray diffraction pattern characterisation, Fourier transform infrared spectroscopy analysis, and magic angle spinning nuclear magnetic resonance analysis. It was found that the strengthening effect of PVA fiber to the geopolymer was primarily a physical strengthening effect, whereas the strengthening effect of carbon nanotubes to the geopolymers was both chemical and physical. Finally, based on the previous study, a multi-scale dual-fibre strengthening mechanism was proposed. Micro-nano fibre composites were used to improve microstructure via physical and chemical effects. This is helpful to improve the performance and application of geopolymers. Furthermore, it lays a preliminary theoretical foundation for engineering applications and technical improvement of geopolymers in the future.